Penerapan Ensemble Characters Dalam Film Pendek Sumpit - Rani Aryani Widjono (ULTIMART Jurnal Komunikasi Visual, 2015)
Short film is an alternative for amateur film makers, who insist with simple short story. The principle of dramatic structure wrapped tightly in three up to 20 minutes of film. That thing, made many film makers choosing a simple structure and only focus for one or two characters. How ever, using more characters creates number of plots, and brings a complex stuffy structure, if it wrapped on 15 minutes film. This article will explain how ensemble charcaters is applied on 16 minutes short film, that entitled Sumpit. Keywords: Short film, ensemble characters, plot, dramatic structure